Factoring Technology in Global Sustainability : A Focus on the Sustainable Development Goals - Shafik, Wasswa (Springer Nature Singapore : Imprint: Springer, 2025)
This book explores the critical role of technology in advancing the United Nations' 2030 Agenda for Sustainable Development. With the world facing pressing challenges like climate change, poverty, and environmental degradation, innovations such as artificial intelligence, big data, the Internet of Things, blockchain, and renewable energy are increasingly shaping global efforts to achieve the Sustainable Development Goals (SDGs). The book examines how these technologies are transforming key sectors, from agriculture and healthcare to energy and education, offering practical solutions to complex global problems. By focusing on each SDG, it provides a thorough look at how technological advancements are being applied to drive sustainable development. Through real-world case studies, the book discusses the practical challenges of scaling and financing these technologies while highlighting the importance of governance, policy, and international cooperation in their success. It also explores how governments, businesses, and global institutions can leverage these innovations to build more resilient and inclusive societies. This book is intended for scholars, policymakers, entrepreneurs, and professionals in sustainability who are seeking a deeper understanding of how technology can be integrated into strategies for achieving the SDGs. As the 2030 deadline approaches, it also offers insights into future trends and emerging technologies that will shape a more sustainable and equitable world in the years to come.
Keywords: Technological innovations.; Sustainability.; Management.; Artificial intelligence.; elektronické knihy; electronic books